Analysis of the overall equipment effectiveness (OEE) and improvement proposals for a steel coil longitudinal cutting machine - Mendonça, Augusto Colombo de; Bagni, Oswaldo Braga; Feroni, Rita de Cassia; Demonel, Wander (Brazilian Journal of Production Engineering, 2025)
Overall Equipment Effectiveness (OEE) is a widely used indicator in industry to measure equipment efficiency, considering three components: availability, performance, and quality. In this context, the present study aims to analyze the OEE of a steel coil longitudinal slitting machine, identifying factors that impact productivity and proposing improvements to the production process performance. The analysis of the first sample period revealed availability, performance, and quality rates of 10.54%, 44.15%, and 98.65%, respectively, resulting in an OEE of 4.59%. Using quality management tools, the main causes of production losses were identified, and improvement measures were proposed. For the second sample period, interventions were implemented, such as scheduling production orders, assigning an additional assistant to the operation, and installing a guide to reduce edge trim jams. As a result, an OEE of 9.52% was obtained, with availability at 20.70%, performance at 46.58%, and quality at 98.69%. The OEE was more than twice as high in the second sample period, suggesting that the implemented improvements were effective and may yield even better results if applied together and associated with medium- and long-term actions.
Keywords: OEE; Performance indicators; Longitudinal slitting machine; Setup time